Coupling scales for modelling heavy metal vaporization from municipal solid waste incineration in a fluid bed by CFD. (September 2015) - Soria, José; Gauthier, Daniel; Flamant, Gilles; Rodriguez, Rosa; Mazza, Germán
Highlights: A CFD two-scale model is formulated to simulate heavy metal vaporization from waste incineration in fluidized beds. MSW particle is modelled with the macroscopic particle model. Influence of bed dynamics on HM vaporization is included. CFD predicted results agree well with experimental data reported in literature. This approach may be helpful for fluidized bed reactor modelling purposes. Abstract: Municipal Solid Waste Incineration (MSWI) in fluidized bed is a very interesting technology mainly due to high combustion efficiency, great flexibility for treating several types of waste fuels and reduction in pollutants emitted with the flue gas. However, there is a great concern with respect to the fate of heavy metals (HM) contained in MSW and their environmental impact. In this study, a coupled two-scale CFD model was developed for MSWI in a bubbling fluidized bed. It presents an original scheme that combines a single particle model and a global fluidized bed model in order to represent the HM vaporization during MSW combustion. Two of the most representative HM (Cd and Pb) with bed temperatures ranging between 923 and 1073 K have been considered. This new approach uses ANSYS FLUENT 14.0 as the modelling platform for the simulations along with a complete set of self-developed user-defined functions (UDFs). The simulation results are compared to the experimental data obtained previously by the research group in a lab-scale fluid bed incinerator. The comparison indicates that the proposed CFD model predicts well the evolution of the HM release for the bed temperatures analyzed. It shows that both bed temperature and bed dynamics have influence on the HM vaporization rate. It can be concluded that CFD is a rigorous tool that provides valuable information about HM vaporization and that the original two-scale simulation scheme adopted allows to better represent the actual particle behavior in a fluid bed incinerator.